Molecular Characterization of Extended-Spectrum Beta-Lactamase Producing Urinary Escherichia coli Isolated in Brong-Ahafo Regional Hospital, Ghana - Wireko, Solomon; Frimpong, E. H.; Feglo, P. K. (European Scientific Journal, ESJ, 2017)
Introduction. Antimicrobial resistance is a growing international problem resulting from the enzyme ?-lactamase production by bacteria, to degrade antibiotics, especially ?-lactam antibiotics. In Brong Ahafo Regional Hospital, Sunyani, these antibiotics are heavily depended upon for the treatment of serious infections, but unfortunately high proportions of bacterial isolates in the hospital, have been found to be resistant to the commonly prescribed antibiotics. This study aims to determine the prevalence of ESBL-producing E. coli so as to determine if ESBL are responsible for the high antimicrobial resistance seen at the Brong-Ahafo Regional Hospital, Sunyani. Methods. The study was a cross sectional study, involving 51 E. coli isolates from urine samples of both in- and out-patients between January and December, 2014. Antimicrobial susceptibility profiles of the isolates were determined by the Kirby Bauer disc diffusion method against 12 antibiotics. The isolates were screened for ESBL production, and then confirmed by the combined disc method. The isolates were tested for the presence of ESBL blaCTX-M and blaTEM by conventional PCR. Results. Non-repeat 1,302 midstream urine samples were cultured from which 200 different pathogens were isolated. Of the 200 isolates 51 were E. coli. Isolates obtained from Community isolates were 16(37.2) and isolates from in-patients were 27(62.8). Resistant strains were detected to all the 12 antimicrobials tested. Low proportions were sensitive to cephalosporins (cefotaxime and ceftazidime), both recording 8/51(15.7%), and quinolones (nalidixic acid and ciprofloxacin), 7/51(13.7%) and 8/51(15.7%) respectively. The isolates had varied susceptibility to aminoglycosides, with low sensitivity of 1/32(2.0%) to gentamicin, but a high proportion of 47/51(92.2%) was sensitive to amikacin. High proportion of the isolates [43/51(84.3%)] were ESBL phenotype, and was found to be significantly associated (p<0.001) with antimicrobial resistance among the isolates. The most prevalent ESBL genotype was BlaTEM with 26 (66.7%) and blaCTX-M 28(71.8%), but 9(23.1%) ESBL phenotypes tested negative for both blaTEM and blaCTX-M genes. 22 (56.4%) of the isolates had both blaTEM and blaCTX-M genes. Conclusion. High proportions of E. coli isolates from urine in Sunyani produce ESBLs. Both blaTEM and blaCTX-M were prevalent and linked to the high levels of drug resistance found in the locality. Increased antibiotic stewardship and stringent infection control measures along with the testing for ESBL must be instituted in the hospital.